Modern input promotion in sub-Saharan Africa: Insights from Asian green revolution - Rashid, Shahidur; Dorosh, Paul A.; Malek, Mehrab; Lemma, Solomon (Wiley, 2013)
Using case materials from four major cereal growing countries in Asia (Bangladesh, India, Indonesia, and Pakistan), the article analyzes key aspects of agricultural input policies in Asia. Results suggest that Asian policies differ from the current wave of African input subsidy programs in three important ways: (i) instead of focusing mostly on seed and chemical fertilizer, input promotion in Asia involved a package approach involving investments in agricultural R&D, irrigation, promotion of domestic fertilizer, and investments in rural roads; (ii) farmers in three of four countries paid higher prices (net taxed) for fertilizer during the height of the green revolution, suggesting that it was the profitability, not the subsidy, that was central to increasing fertilizer use; and (iii) Asian countries did not target input subsidies, but given leakage and diversion estimates of targeted programs, it is unclear whether targeting would have been more cost‐effective. Both continents have two challenges in common: degradation of soil health and increasingly larger shares of public spending on input subsidies. The first challenge calls for paying attentions to improving fertilizer use efficiency, which is an achievable target, with high pay off in the long run. The other challenge is now a historical fact—that is, once introduced, subsidies are hard to eliminate, even if they no longer contribute to agricultural productivity growth.